Integrated Resistivity, Index, and Strength Characteristics of Subgrade Soils: Implication for Highway Pavement Failure Studies in North-Central Nigeria - OBASAJU, Daniel Opemipo; OLORUNTOLA, Moroof Olasunbo; OLADELE, Sunday (GeoScience Engineering, 2022)
Integrated geophysical and geotechnical studies have been carried out to determine the geological cause(s) of the failure of sections of Ajaokuta – Anyigba Highway, North-central Nigeria. Forty-eight (48) Vertical Electrical Soundings (VES) were conducted on failed and stable sections of the highway. Also, twenty-one (21) subgrade soil samples close to VES stations from the unstable and stable sections of the highway were subjected to laboratory geotechnical analyses which include grain size distribution, Atterberg limits, compaction (Optimum Moisture Content, OMC, and Maximum Dry Density, MDD) and California bearing ratio (CBR) at soaked and unsoaked states following American Society for Testing and Material (ASTM) standards as appropriate. The geophysical results show that low resistivity (10–100 Ohms-m) inferred as clay/silt of low competence characterizes the subgrade soils of the unstable segment. While higher resistivity (148–272 Ohms-m) interpreted as sandy-clay/silt with moderate competence was obtained for the subgrade soils of the stable segment. Results of Geotechnical tests show that the subgrade soils of the unstable segment have geotechnical properties that generally fall below required standard specifications. Strong correlations of R = 0.86, 0.9, and –0.88 were obtained between CBR and sand, resistivity, and the amounts of fines, while a fairly strong correlation of R = –0.67 was obtained for the plasticity index. The high level of correlation implies that CBR can be predicted from geophysical data and other geotechnical parameters. The study has revealed that the advanced weathering of the underlying Mica-Schist to clayey/silty subgrades with unsuitable geophysical and geotechnical properties is a major contributor to the instability of the highway. Keywords: Atterberg limit; CBR; Grain size distribution; Resistivity; Subgrade soil.